PERAN SERTA MASYARAKAT DAERAH BANTARAN SUNGAI BADUNG DALAM PENANGANAN DAN PENGELOLAAN SAMPAH DI WILAYAH KOTA DENPASAR - Ade Wihendra, Ida Bagus; Wairocana, I Gusti Ngurah; Dahana, Cokorda Dalem (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
The Law Number 18 year 2008 concerning Trashand Law Number 32 year 2009 concerning Environment have similarly regulate the participation of the community. It because community participation hold important role to handle and manage the trash. If the community didn’t have role, than the government will be working alone to handle and manage the trash. Trash is produced by the community and that is why the community has to hold role to handle and manage the trash. Trash is never endings problem, that is the problem that owned by all people. Healthy Environment is right of every people, to make healthy environment is required to have the cooperation on the terms of law about environment and trash namely Law number 18 year 2008 About Trash and Law Number 32 year 2009 about environment. Trash in Badung River is problem, important problem, but there is no concern about it.
Keywords: Community Participation, Trash, Management, and Handling